Antibacterial activity of sponge-associated bacteria from Torosiaje marine area, Gorontalo, Indonesia - YULIANA RETNOWATI; ABUBAKAR SIDIK KATILI (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Retnowati Y, Katili AS. 2023. Antibacterial activity of sponge-associated bacteria from Torosiaje marine area, Gorontalo, Indonesia. Biodiversitas 24: 1151-1156. The marine sponge is a member of the Porifera class animal group that has the potential to produce secondary metabolites with various biological activities. These marine animals are often associated with various bacteria from the actinomycetes and non-actinomycetes groups. Currently, information about bacteria associated with sponges in Gorontalo coastal waters is still very limited. Bacteria associated with organisms from the marine environment have been explored as producers of new types of bioactive compounds. Exploring bacteria associated with sponges in the coastal waters of Gorontalo can potentially find new types of antibiotics. The aim of this study was to reveal the diversity of antibiotic-producing bacteria associated with sponges in the Torosiaje coastal area, Gorontalo. The research was carried out in the Torosiaje marine area as sponge sampling locations, including seawater physicochemical properties measurement. The sponges were identified based on morphological characteristics. The sponge-associated bacteria were isolated and screened for antibacterial potential against Escherichia coli and Staphylococcus aureus. The potential sponge-associated bacteria were identified based on a molecular approach. The result showed that a total of 10 sponge members of Demospongiae class. All ten sponge-associated bacteria were non-actinomycetes bacterial isolates that showed similar morphological characteristics. Only isolate ILM-1 associated with Coelocarteria singaporensis showed antibacterial potential in broad-spectrum mode against Escherichia coli and Staphylococcus aureus. The ILM-1 isolate was identified as Vibrio diabolicus closely related to Vibrio diabolicus strain CW-9-11-1 with a similarity index of 99.70%.